Development of a Gerontology Counseling Competency Model: A Need Analysis Study - Nik Nazlan Nik Jafar; Pau Kee; Aslina Ahmad (International Journal of Education, Information Technology, and Others, 2023)
Malaysia is projected to attain the status of an aging nation by 2030, with its elderly population encountering unique mental health challenges. Consequently, counselors need to possess specialized competencies to effectively fulfill their roles and responsibilities in assisting elderly clients. This study aimed to assess the necessity of developing a gerontology counseling competency model specifically tailored for counselors working with older adults. The research employed a Design and Development Research approach with a fully qualitative method in the need analysis phase, with semi-structured interviews involving 15 registered counselors who met predefined criteria. Thematic analysis of the interviews was conducted, and the findings unveiled a concerning gap in the availability of structured or specialized gerontology counseling courses, both at the undergraduate and graduate levels. Furthermore, there is a noticeable dearth of in-service training opportunities tailored specifically for gerontology counseling, which strongly supports the need for such a model that would serve as a valuable reference and set of guidelines for counselors. This model is expected to elevate the professionalism of counselors when working with elderly individuals, highlighting the growing importance of counselors in actively promoting the well-being of older adults, in alignment with the 2011 Malaysian National Policy for Older Persons.